Comparative analysis of the driving forces and spatiotemporal patterns of urbanisation in Muscat, Doha, and Dubai. Issue 5 (4th July 2019) - Abulibdeh, Ammar; Al-Awadhi, Talal; Al-Barwani, Mohammed
ABSTRACT: This article analyses contemporary urbanisation patterns in Muscat, Dubai, and Doha cities, focusing on urban land cover change and the roles of governance, globalisation, oil revenues, internal migration, social factors, and urban planning forces in developing these cities. Remotely sensed and demographic data for the past 30 years were used to identify concurrent changes in urbanisation patterns, in order to gain a comprehensive understanding of the dynamics of urbanisation. The results show that the three cities have all experienced unprecedented urban transformation, with high urbanisation and population growth, but with differences in the patterns of development.